Visualising a rare and complex case of advanced hilar cholangiocarcinoma. (2nd January 2017) - Qu, Jia; Fung, Albert; Kelly, Paul; Tait, Gordon; Greig, Paul D.; Agur, Anne; McGilvray, Ian D.; Jenkinson, Jodie
Abstract: The Toronto Video Atlas of Liver, Pancreas, Biliary, and Transplant Surgery (TVASurg) is a free online library of three-dimensional (3D) animation-enhanced surgical videos, designed to instruct surgical fellows in hepato-pancreato-biliary (HPB) and transplant procedures. The video 'Klatskin tumours: Extended left hepatectomy with complex portal vein reconstruction and in situ cold perfusion of the liver', which is available to watch athttp://TVASurg.ca, is a unique and valuable visual resource for surgeons in training to assist them in learning this rare procedure. This paper describes the methodologies used in producing this 3D animation-enhanced surgical video.